Child and adolescent behavioral health - Yearwood, Edilma Lynch; Pearson, Geraldine S.; Newland, Jamesetta A. (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
'As an increasing number of children and adolescents with psychiatric symptoms go unrecognized in our current healthcare system, the ability to identify and treat these issues in multiple healthcare settings has become vitally important. With access to primary care providers increasing and a shortage of child psychiatric providers, collaboration between psychiatric, pediatric and family advanced practice nurses is essential to improving care for this vulnerable population. Child and Adolescent Behavioral Health provides a practical reference to aid in this endeavour. Written and reviewed by over 70 nurse experts, it is a must-have reference for all practitioners caring for children and adolescents.'
Section 1. Assessment -- section 2. Treatment -- section 3. Special populations -- section 4. Special issues.
Includes bibliographical references and index.
Electronic resource; title from digital home page.
Keywords: Child mental health; Pediatric nursing; Psychiatric nursing; Child; Mental disorders; Adolescent; Advanced Practice Nursing; Nursing Assessment -- methods; Primary Care Nursing; Psychiatric Nursing; HEALTH & FITNESS -- Children's Health; MEDICAL -- Pediatrics; Child mental health; Pediatric nursing; Psychiatric nursing; Electronic books